Color-motion feature binding occurs unconsciously. (14th May 2018) - Chen, Jiacheng; Chen, Yifan; Liu, Ying
Highlights: Feature binding itself does not necessarily lead to the establishment of visual consciousness. We manipulated the visibility of priming stimuli, which consisted of color-motion features. We then measured the effects of manipulation of visibility on reporting of cued targets' direction of rotation. A priming effect was observed even when the priming stimuli were invisible. The color-motion features of the prime could bind unconsciously. Abstract: The relationship between consciousness and feature binding has long been a topic of debate. Although they may be associated, there is growing evidence supporting the notion that feature binding and visual consciousness can be separated to some degree. In our study, we manipulated the visibility of priming stimuli, which consisted of color-motion features, and then measured the effects of those manipulations on reporting of cued targets' direction of rotation. A priming effect was observed even when the priming stimuli were invisible, implying that the color-motion features of the prime could bind unconsciously. These findings support the notion that, at least under certain conditions, feature binding and visual consciousness are separable psychological processes wherein feature binding is not sufficient to establish visual awareness.